2020
DOI: 10.1245/s10434-020-08904-w
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Evaluation of the Potential Anatomic Pathways of Systemic Metastasis from Primary Breast Cancer Suggests an Orderly Spread Through the Regional Lymph Nodes

Abstract: Background Two conflicting hypotheses as to how breast cancer (BC) accesses the systemic circulation dominated the 20th century and affected surgical treatment. We hypothesized that tumor lymphovascular invasion (LVI) at the primary tumor site favors lymphatic and not blood vessel, capillaries, and systemic metastases (Smets) are dependent upon regional lymph node (RLN) mets. Methods Data from BC patients undergoing RLN biopsy was professionally abstracted and maintaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Meanwhile, as results of univariate and multivariate Cox regression analyses suggested, occupation, US-LNM, US-BIRADS, clinical T stage, clinical N stage, clinical TNM stage, tumor size, pathological T stage, postoperative endocrine therapy, postoperative targeted therapy, and lymph vessel invasion were significant prognostic factors in predicting patients’ improved DFS and OS. Lymph vessel invasion is thought to play an important role in tumor metastasis, and acts as the modulation of antitumor immune responses ( David Nathanson et al, 2020 ; Testa et al, 2020 ; Wang et al, 2020 ). The tumor angiogenesis and its indicative vascular density are closely related to the prognosis of breast cancer ( Huang et al, 2020 ; Koch et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, as results of univariate and multivariate Cox regression analyses suggested, occupation, US-LNM, US-BIRADS, clinical T stage, clinical N stage, clinical TNM stage, tumor size, pathological T stage, postoperative endocrine therapy, postoperative targeted therapy, and lymph vessel invasion were significant prognostic factors in predicting patients’ improved DFS and OS. Lymph vessel invasion is thought to play an important role in tumor metastasis, and acts as the modulation of antitumor immune responses ( David Nathanson et al, 2020 ; Testa et al, 2020 ; Wang et al, 2020 ). The tumor angiogenesis and its indicative vascular density are closely related to the prognosis of breast cancer ( Huang et al, 2020 ; Koch et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with BC with positive regional LNs have higher rates of systemic metastasis compared with those with node-negative disease. 98 Furthermore, patients with BC with LN micrometastasis (<2 mm) have a reduced incidence of distant metastasis compared with patients with macrometastasis. 99 Several studies found that patients with extracapsular extension, the growth of cancer cells outside the LN capsule, have poor prognosis 100 and thus patients with macroscopic extranodal disease may benefit from axillary LN dissection to prevent locoregional recurrence.…”
Section: Breast Cancer Cells In Lymph Nodes and Beyondmentioning
confidence: 99%
“…NGS can reveal novel insights regarding tumor heterogeneity, clonal evolution, and the metastatic process [4]. Primary and locally relapsed breast tumors usually have similar genomic profiles and morphology, suggesting that the metastasis originated from the primary tumor [5]; however, differences in biomarker expression [6], degree of lymphovascular invasion [7], and progression of histologic grade [8] can occur between the primary tumor and recurrent or distant metastatic breast tumors.…”
Section: Molecular Tumor Boardmentioning
confidence: 99%